Sources and Fluxes of Organic Carbon and Energy to Microorganisms in Global Marine Sediments - Bradley, James A.; Arndt, Sandra; Amend, Jan P.; Burwicz-Galerne, Ewa; LaRowe, Douglas E. (Frontiers in Microbiology, 2022)
Marine sediments comprise one of the largest microbial habitats and organic carbon sinks on the planet. However, it is unclear how variations in sediment physicochemical properties impact microorganisms on a global scale. Here we investigate patterns in the distribution of microbial cells, organic carbon, and the amounts of power used by microorganisms in global sediments. Our results show that sediment on continental shelves and margins is predominantly anoxic and contains cells whose power utilization decreases with sediment depth and age. Sediment in abyssal zones contains microbes that use low amounts of power on a per cell basis, across large gradients in sediment depth and age. We find that trends in cell abundance, POC storage and degradation, and microbial power utilization are mainly structured by depositional setting and redox conditions, rather than sediment depth and age. We also reveal distinct trends in per-cell power regime across different depositional settings, from maxima of ∼10–16 W cell–1 in recently deposited shelf sediments to minima of <10–20 W cell–1 in deeper and ancient sediments. Overall, we demonstrate broad global-scale connections between the depositional setting and redox conditions of global sediment, and the amounts of organic carbon and activity of deep biosphere microorganisms.